2021
DOI: 10.3390/jpm11030192
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Genetic Variations in the Kynurenine Pathway for Interferon-α-Induced Depression in Patients with Hepatitis C Viral Infection

Abstract: Importance: The high incidence of major depressive episodes during interferon-α (IFN-α) therapy is considered the most powerful supportive evidence for the inflammation theory of depression. As the kynurenine pathway plays an important role connecting inflammation and depression, it is plausible to investigate this pathway for predictive genetic markers for IFN-α-induced depression. Methods: In this prospective case-control study, we assessed 291 patients with chronic hepatitis C viral infection taking IFN-α t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The genome-wide permutations process powered by an accelerated expectation-maximization algorithm [34] or SNPs and haplotypes has been recognized as a valid predictor for the effects of multiple genes and linkage disequilibrium [35,36]. For instance, previous studies provided evidence suggesting the possible pathology of the kynurenine pathway [10] and the ionotropic glutamate receptor pathways [11] in MDD. Furthermore, to evaluate the combination effect of each SNP in the same gene, we carried out the haplotype association tests with Haploview 4.2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome-wide permutations process powered by an accelerated expectation-maximization algorithm [34] or SNPs and haplotypes has been recognized as a valid predictor for the effects of multiple genes and linkage disequilibrium [35,36]. For instance, previous studies provided evidence suggesting the possible pathology of the kynurenine pathway [10] and the ionotropic glutamate receptor pathways [11] in MDD. Furthermore, to evaluate the combination effect of each SNP in the same gene, we carried out the haplotype association tests with Haploview 4.2.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) provide insights for the exploration of potential pathological genes in MDD. For instance, based on GWAS, genes such as Kynureninase (KYNU), Sirtuin (SIRT), glutamate ionotropic receptor AMPA type subunit 2 (GluR2), Neuronal Growth Regulator 1 (NEGR1), and High Mobility Group Box 1 (HMGB1) may relate to depressive symptoms [6][7][8][9][10][11]. Some of these aforementioned genes, including KYNU and SIRT, are also associated with NAD.…”
Section: Introductionmentioning
confidence: 99%
“…In follow-ups these individuals have shown to be prone to relapse into new depressive episodes ( 101) -hypothetically triggered by major stressful events or major infections. Genetic studies have also suggested that patients that develop depression under IFN-α have higher frequencies of certain genetic variations, single nucleotide polymorphisms (SNPs), associated to glutamate receptor pathways and kynurenine pathways (102,103). This could support the theory that individuals genetically predisposed may react to inflammation with changes in 5-HT levels or glutamate levels in the brain.…”
Section: Study IImentioning
confidence: 92%
“…However, in a situation of increased activation of the immune system, inflammatory factors cause excessive activation of IDO (indoleamine-2,3-dioxygenase), an enzyme present in microglia, astrocytes and neurons, catabolizing the transformation of tryptophan into the neurotoxic kynurenine (KYN), thereby reducing the availability of tryptophan for the production of serotonin. Kynurenine, in turn, influences the intensification of neurodegenerative processes [ 6 ].…”
mentioning
confidence: 99%